Раннеземледельческое поселение в Северной Месопотамии - Мунчаев, P. M.
Munčaev, R. M. - Bader, N. О.,Eine frühagrarische Siedlung in Nordmesopotamien; Теll Magzalia; cf. SAr 2/1979, 117-132; engl. Résumé.